Caries detection in primary teeth is less challenging than in permanent teeth - Fausto M Mendes; Mariana M Braga (Dental Hypotheses, 2013)
Introduction: Most studies about caries detection methods have been performed using permanent teeth. Primary teeth, however, present significant differences from permanent teeth; hence findings of these studies with permanent teeth cannot be extrapolated. The Hypothesis: Our hypothesis is that the caries diagnosis process in primary teeth is less challenging than in permanent teeth. This assertion is based on the fact that primary enamel is thinner and the caries process progresses faster in this type of teeth when compared to permanent teeth. For these reasons, the majority of caries lesions in primary teeth would be more evident and therefore, easily detected through visual inspection. Only a few number of caries lesions would be missed by visual inspection. Thus, adjunct diagnostic methods, such as radiographs, would be unnecessary for primary teeth. Evaluation of the Hypothesis: To evaluate this hypothesis, researchers should conduct studies about the performance of the caries detection methods avoiding selection bias and defining appropriate settings. Clinical trials randomizing the diagnostic strategies would be worthwhile. The evidence supporting the benefits of adjunct methods in detecting caries lesions in primary lesions is limited. However, clinical guidelines have recommended the use of the radiographic method to detect caries in primary teeth in all symptomless children. The confirmation of our hypothesis would lead to the need to re-evaluate such guidelines.